PENGARUH KUALIATAS PELAYANAN ISLAMI DAN KEPUASAN TERHADAP LOYALITAS MENABUNG NASABAH DI BMT UGT NUSANTARA CABANG PEMBANTU TEMUGURUH KABUPATEN BANYUWANGI - Adi Nur Cahyo; Munawir (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This research aims to analyze the influence of: 1) Islamic Service Quality (X1) has a positive and significant effect on Customer Savings Loyalty (Y). 2) To analyze Satisfaction (X2) which has a positive and significant effect on Customer Savings Loyalty (Y). 3) To analyze the Quality of Islamic Service (X1) and Satisfaction (X2) which have a positive and significant effect simultaneously or together on Customer Savings Loyalty (Y) at BMT UGT Nusantara Temuguruh Sub-Branch, Banyuwangi Regency. The results of multiple linear regression analysis show that: 1) Islamic Service Quality (X1) has a positive and significant effect on Customer Savings Loyalty (Y). 2) Satisfaction (X2) has no positive and significant effect on Customer Savings Loyalty (Y). 3) There is a simultaneous positive and significant influence between the Islamic Service Quality (X1) and Satisfaction (X2) variables on the Customer Savings Loyalty variable (Y).